2023
DOI: 10.1021/acs.accounts.2c00690
|View full text |Cite
|
Sign up to set email alerts
|

Layered Oxide Cathodes for Sodium-Ion Batteries: Storage Mechanism, Electrochemistry, and Techno-economics

Abstract: Conspectus Lithium-ion batteries (LIBs) are ubiquitous in all modern portable electronic devices such as mobile phones and laptops as well as for powering hybrid electric vehicles and other large-scale devices. Sodium-ion batteries (NIBs), which possess a similar cell configuration and working mechanism, have already been proven as ideal alternatives for large-scale energy storage systems. The advantages of NIBs are as follows. First, sodium resources are abundantly distributed in the earth’s crust. Second, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
73
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(106 citation statements)
references
References 56 publications
0
73
0
1
Order By: Relevance
“…It is widely reported that the instability of transition metal oxides toward moisture leads to the great deterioration of electrochemical performance, which hinders the practical application of transition metal oxides. [ 24,50,51 ] To investigate the effect of the hydration/dehydration process on the electrochemical properties of the NMO‐1W‐D, the half‐cells based on the NMO‐1W‐D were assembled and evaluated. Interestingly, the dehydration NMO‐1W‐D electrode shows similar CV curves to the pristine NMO‐1 W ( Figure 6 a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely reported that the instability of transition metal oxides toward moisture leads to the great deterioration of electrochemical performance, which hinders the practical application of transition metal oxides. [ 24,50,51 ] To investigate the effect of the hydration/dehydration process on the electrochemical properties of the NMO‐1W‐D, the half‐cells based on the NMO‐1W‐D were assembled and evaluated. Interestingly, the dehydration NMO‐1W‐D electrode shows similar CV curves to the pristine NMO‐1 W ( Figure 6 a).…”
Section: Resultsmentioning
confidence: 99%
“…[ 23 ] Nonetheless, the P2‐Na x MnO 2 compounds are still haunted by irreversible structural changes/phase transitions during cycling, insufficient electrochemical performances, and air/moisture instability. [ 24–26 ]…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these Mn oxides could be applied in the synthesis of new composites, sodium-ion batteries, oxidation, removal of toxic ions, catalysts, supercapacitors, and sensors …”
Section: Resultsmentioning
confidence: 99%
“…Other strategies with these Mn oxides could be also promising to investigate WOR activity. 82−86 In addition, these Mn oxides could be applied in the synthesis of new composites, 87 sodium-ion batteries, 88 oxidation, 89 removal of toxic ions, 90 catalysts, 91 supercapacitors, 92 and sensors. 93…”
Section: ■ Introductionmentioning
confidence: 99%
“…The research interest in sodium insertion materials has been totally renewed as a result of the current conditions, which include energy difficulties and an increase in demand for large-scale batteries. After 2010, material research explored new sodium insertion materials for battery applications [5][6][7][8][9][10][11][12][13][14]. Some layered transition metal oxides have received a lot of attention as cathode materials for sodium ion batteries because they are sodium intercalation host materials [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%